Sally Swartz, Homeless Wanderers: Movement and Mental Illness in the Cape Colony in the Nineteenth Century: A nuanced exploration of the Cape Colony’s psychiatry system (Historia, 2021)
Sally Swartz's Homeless Wanderers: Movement and Mental Illness in the Cape Colony in the Nineteenth Century, explores the history of insanity in the Cape Colony and in extension the British Empire between 1890 and 1910. This was a period of massive social change due to the rise of immigration, and as will be shown in this review, policing of the insane was central to sustaining colonial settler identity. Thus, in 1890, the Cape Colony restructured its system of surveillance and confinement of mentally ill patients.